Delay-sensitive data allocation scheme for CMT over diversity paths - Wen-feng DU; Zhen WU; Li-qian LAI (Tongxin xuebao)
The performance of CMT association degrades remarkably when the performances of parts of paths deteriorate.Based on the analysis of different network configurations,a delay sensitive data allocation scheme was proposed to distribute data to different paths over multi-diversity network with reference of their transmission delay,which is a key factor to the whole performance.Meanwhile,the transmission sequence number of each chunk will also was considered.The result of analysis and simulation reveal the performance of our scheme can achieve much better performance than the original round-robin scheme.